2007
DOI: 10.1080/09712119.2007.9706638
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role in the Small Ruminant Sector in Mountain Area of Turkey

Abstract: Davran, M.K., Darcan, N . and Budak, D.B. 2007. Gender role in the small ruminant sector in mountain area of Turkey. J. Appl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Women working in these production units totalled an average of 4.9 ± 2.9 h/day (Table 4). This value is lower than that found in other Mediterranean countries, i.e., Turkey, where women working on small ruminant farms devote 12.6 h/day to working with animals, mainly grazing them [15]. However, as has been mentioned previously, only 46.2% of the farms studied (the semi-extensive ones) had grazing activity; and this exclusively corresponded to men.…”
Section: Division Of Work On Dairy Goat Production Unitscontrasting
confidence: 54%
See 1 more Smart Citation
“…Women working in these production units totalled an average of 4.9 ± 2.9 h/day (Table 4). This value is lower than that found in other Mediterranean countries, i.e., Turkey, where women working on small ruminant farms devote 12.6 h/day to working with animals, mainly grazing them [15]. However, as has been mentioned previously, only 46.2% of the farms studied (the semi-extensive ones) had grazing activity; and this exclusively corresponded to men.…”
Section: Division Of Work On Dairy Goat Production Unitscontrasting
confidence: 54%
“…Female herders, however, received fewer services, and the veterinary clinics proved to be less beneficial for them. In rural regions of Turkey, where small ruminant farming plays an important social role, the distribution of the work was unfavourable to women, with their position in decision-making processes being secondary [15]. On the contrary, Verbeek et al [16] suggested that women who work in goat-intensive small farms in Kenya participated in a greater proportion of the herd's reproductive management compared with women who work in goat-extensive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mountain women work on average 10.3 h/day in animal production as an unpaid family labour force (Kantar 1996). According to many researchers, women play a major role in smallruminant production (Sinn et al 1999;Valvidia et al 1996;Gidarakou 1999;Shorthall 2000;FAO 2005;Davran et al 2007;Rousan 2007).…”
Section: Introductionmentioning
confidence: 97%